Spatial Autocorrelation Analysis of Rice Production in Indonesia in 2024 - Hendryati Rahmi; Muhammad Azhar; A Fahmi Indrayani (Jurnal Geografika (Geografi Lingkungan Lahan Basah), 2025)
Rice production is an essential component of Indonesia's agricultural sector and plays a vital role in maintaining national food security. However, the distribution of rice production across provinces remains spatially uneven, influenced by differences in geography, climate, and agricultural infrastructure. This study aims to analyze the spatial autocorrelation of rice production in Indonesia and to identify regional clustering patterns based on production levels. The research employs a quantitative descriptive approach, incorporating spatial analysis methods such as Moran's I and Local Indicators of Spatial Association (LISA), utilizing GeoDa software. Data were obtained from Statistics Indonesia (BPS) and provincial administrative boundary maps. The results indicate a positive spatial autocorrelation with a Moran's I value of 0.2163 and a p-value of 0.018, implying that provinces with high production tend to be located near other high-producing provinces. High–High clusters were found in West Java, Central Java, and West Nusa Tenggara, while Low–Low clusters appeared in Papua and Maluku. Additionally, Low–High clusters were identified in Banten, East Java, and Bali, indicating provinces with relatively low production surrounded by high-producing neighbors. No High–Low clusters were detected during the observation period. These findings show that rice production in Indonesia remains spatially uneven.